The Scarlet Rose. #4, "You will always be mine" - Lyfoung, Patricia (Charmz, 2019)
As Maud and Guilhem prepare for their wedding, Natalia blackmails Guilhem into stealing with her and leaving for Russia to find out the truth about his father. Maud leaves in search of Guilhem to find out why he left her.